Comparison of a Performance-Based Test Results with Two Self-Reported Questionnaires in Determining the Rate of Disability in Patients with Chronic Low Back Pain - Seyed Ali Reza Derakhshan-Rad; Ali Ghanbari; Maryam Sheikhi; Seyed Mohamad Derakhshan- Rad (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: self-reported questionnaires and performance-based tests are the two methods of measuring the rate of disability in patients with chronic low back pain. The goal of this research was study of the influence of pain on these patients' disability rate by comparing the findings of Roland-Morris Disability questionnaire (RMDQ) and Oswestry Disability Index (ODI) self-reported questionnaires with a performance-based test named Back Performance Scale (BPS). Methods and materials: This research is a cross sectional study and the study population were patients with nonspecific chronic low back pain. 75 patients 18 to 60 year-old age were enrolled through a convenient sampling. Back Performance Scale and the RMDQ and ODI questionnaires used to assess disability and the pain intensity was measured with VAS. Spearman correlation coefficient used for determining the correlation between pain and disability, and Pearson correlation coefficient used to determine the correlation between different modes of disability instruments. T-test used to compare the differences in disability rate between two groups of mild to moderate pain and severe pain. Results: The correlation coefficients between VAS and BPS, RMDQ and ODI were 0.37, 0.55 and 0.54 respectively (P<0.01), and correlation coefficients between BPS and RMDQ and ODI were 0.41 and 0.52 (P<0.001). Back Performance Scale showed no significant difference between two pain groups (P=0.139) but this difference was significant in the questionnaire results (P<0.01). Conclusion: Dissidence and the moderate correlation between the results of the self-reported questionnaires and Back Performance Scale showed that two methods of measures could represent different aspects in producing disability. Hence, making use of both instruments simultaneously is recommended to draw a holistic outline of the patients' functional status.